An eucharistic miracle between Galicia and Portugal: sources and contexts of the Cantiga de Santa María 104 - Negri, Manuel (Madrygal. Revista de Estudios Gallegos, 2020)
The Cantigas de Santa María, composed and compiled in the second half of the XIIIth century by Alphonse X and his collaborators, contain some miracles on a subject of great relevance to the time of the Wise King, that is to say, the Eucharistic theme. In those texts, men and women experience the transformation of the consecrated hosts into meat and blood, thus realizing outside the principles of the transubstantiation dogma. After a census of these Cantigas, all problematic as regards the determination of their sources, the case of the Cantiga de Santa María 104 will be discussed, for which Jaime Ferreiro Alemparte and José Filgueira Valverde thought of a written model in the work of the German Cesario of Heisterbach and a Galician transmission channel, if we consider the location of the story: Caldas de Reis. Through a renewed comparative study between the Galician-Portuguese text and the tradition of reference, we come to an alternative hypothesis to that of the two previous specialists. It establishes different levels and areas of influence in each section of the miracle from Pier Damani’s Opuscula and the narrative model of the Santíssimo Milagre de Santarém. Finally, thanks to this hypothesis, new considerations are going to be provided about the entry period of the miracle in the court and the political and doctrinal reasons that would have made it possible